2001
DOI: 10.1590/s0100-879x2001001100018
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant action of Polypodium leucotomos extract and kojic acid: reactions with reactive oxygen species

Abstract: Two natural products Polypodium leucotomos extract (PL) and kojic acid (KA) were tested for their ability to scavenge reactive oxygen species (in phosphate buffer. Hydroxyl radicals were generated by the Fenton reaction, and the rate constants of scavenging were 1.6 x 10 9 M -1 s -1 for KA and 1.0 x 10 9 M -1 s -1 for PL, similar to that of ethanol (1.4 x 10 9 M -1 s -1 ). With superoxide anions generated by the xanthine/hypoxanthine system, KA and PL (0.2-1.0 mg/ml) inhibited · O 2 -dependent reduction of nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 33 publications
(36 reference statements)
3
59
0
3
Order By: Relevance
“…15 In vitro studies have shown that PL acts as an effective antioxidant by quenching superoxide anion, singlet oxygen, lipid peroxides, and the hydroxyl radical. 16,17 Previous studies showed that topical and oral PL decreased acute sunburn response and resulted in Langerhans cell preservation of human skin when exposed to sunlight 18 and psoralen-UVA. 19 The goal of this study was to further analyze the ability of orally administered PL to decrease UV-induced erythema and the resulting histologic skin damage under carefully controlled laboratory conditions.…”
mentioning
confidence: 99%
“…15 In vitro studies have shown that PL acts as an effective antioxidant by quenching superoxide anion, singlet oxygen, lipid peroxides, and the hydroxyl radical. 16,17 Previous studies showed that topical and oral PL decreased acute sunburn response and resulted in Langerhans cell preservation of human skin when exposed to sunlight 18 and psoralen-UVA. 19 The goal of this study was to further analyze the ability of orally administered PL to decrease UV-induced erythema and the resulting histologic skin damage under carefully controlled laboratory conditions.…”
mentioning
confidence: 99%
“…* High doses of omega-3 polyunsaturated fatty acids from fish oil have been shown to decrease UVB induced erythema and inflammation [46]. * Polypodium leucotomos extract (PL) can also be administered orally with very low toxicity, in addition to its topical use as already described.Oral PL scavenges free radicals and reactive oxygen species such as superoxide anion, singlet oxygen, hydroxyl radical and hydrogen peroxide, and prevents lipid peroxidation [47,48]. Besides the effects already mentioned, PL also prevents oxidative DNA damage (8-hydroxyguanine) and accelerates repair of thymine dimers [24,49].…”
Section: Systemic Sunscreensmentioning
confidence: 98%
“…Percentage inhibition of deoxyribose degradation was calculated. Quercetin was used as standard (Gomes et al, 2001). …”
Section: Deoxyribose Degradation Assay (Hydroxyl Radical Scavenging Amentioning
confidence: 99%
“…They are dangerous; however, when present in excess, they can attack biological molecules such as lipids, proteins, enzymes, DNA and RNA, leading to cell or tissue injury (Amarowicz et al, 2004). The cells experience an oxidative stress which contributes in various clinical disorders such as cancer, heart diseases, neurogenerative diseases like multiple sclerosis, Parkinson`s disease, autoimmune disease, stroke, arthritis, ischemia, reperfusion injury, acute hypertension, haemorrhagic shock, emphysema, cirrhosis, diabetes mellitus, hepatitis, cancer, atherosclerosis as well as other ailments (Roome et al, 2008;Ajith et al, 2002;Gomes et al, 2001;Kang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%